The association between treatment adherence to nicotine patches and smoking cessation in pregnancy - Vaz, Luis R.; Aveyard, Paul; Cooper, Sue; Leonardi-Bee, Jo; Coleman, Tim (2016)
Background: In non-pregnant “quitters,” adherence to nicotine replacement therapy (NRT) increases smoking cessation. We investigated relationships between adherence to placebo or NRT patches and cessation in pregnancy, including an assessment of reverse causation and whether any adherence: cessation relationship is moderated when using nicotine or placebo patches.